Summing Factorials

Calculus Level 4

The value of

1 1 ! ( 1 + 1 ! ) ( 1 + 2 ! ) + 2 2 ! ( 1 + 2 ! ) ( 1 + 3 ! ) + 3 3 ! ( 1 + 3 ! ) ( 1 + 4 ! ) + 2014 2014 ! ( 1 + 2014 ! ) ( 1 + 2015 ! ) \dfrac{1 \cdot 1!}{(1+1!)(1+2!)}+\dfrac{2 \cdot 2!}{(1+2!)(1+3!)}+\dfrac{3 \cdot 3!}{(1+3!)(1+4!)}+ \cdots\frac{2014\cdot2014!}{(1+2014!)(1+2015!)}

can be expressed in the form A ! A ! + 1 B C , \dfrac{A!}{A!+1}-\dfrac{B}{C}, where A , B A,B and C C are coprime positive integers, and A > B , C . A>B,C. Find the value of A + B 2 C . \dfrac{A+B}{2C}.


The answer is 504.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Pratik Shastri
Oct 16, 2014

S = 1 1 ! ( 1 + 1 ! ) ( 1 + 2 ! ) + 2 2 ! ( 1 + 2 ! ) ( 1 + 3 ! ) + 3 3 ! ( 1 + 3 ! ) ( 1 + 4 ! ) + 2014 terms = r = 1 2014 [ r r ! ( 1 + r ! ) ( 1 + ( 1 + r ) ! ) ] \begin{aligned} S &=\dfrac{1 \cdot 1!}{(1+1!)(1+2!)}+\dfrac{2 \cdot 2!}{(1+2!)(1+3!)}+\dfrac{3 \cdot 3!}{(1+3!)(1+4!)}+ \cdots \text{2014 terms} \\ \\ &=\sum_{r=1}^{2014}\left[ \dfrac{r \cdot r!}{(1+r!)(1+(1+r)!)}\right] \end{aligned} Then write the r r in the numerator as ( r + 1 ) ! + 1 ( r + 1 ) ! 1 + r . (r+1)!+1-(r+1)!-1+r. Doing so, we get S = r = 1 2014 [ r ! ( r + 1 ) ! + 1 ( r + 1 ) ! 1 + r ( 1 + r ! ) ( 1 + ( 1 + r ) ! ) ] = r = 1 2014 [ r ! ( r + 1 ) ! + r + 1 ( r + 1 ) ! 1 ( 1 + r ! ) ( 1 + ( 1 + r ) ! ) ] = r = 1 2014 [ r ! ( r + 1 ) ( r ! + 1 ) ( r + 1 ) ! 1 ( 1 + r ! ) ( 1 + ( 1 + r ) ! ) ] = r = 1 2014 [ r ! ( ( r + 1 ) 1 + ( r + 1 ) ! 1 1 + r ! ) ] = r = 1 2014 [ ( r + 1 ) ! 1 + ( r + 1 ) ! r ! 1 + r ! ] \begin{aligned} S&=\sum_{r=1}^{2014}\left[r! \cdot\dfrac{(r+1)!+1-(r+1)!-1+r}{(1+r!)(1+(1+r)!)}\right]\\ \\ &=\sum_{r=1}^{2014}\left[r!\cdot\dfrac{(r+1)!+r+1-(r+1)!-1}{(1+r!)(1+(1+r)!)}\right]\\ \\ &=\sum_{r=1}^{2014}\left[r! \cdot\dfrac{(r+1)(r!+1)-(r+1)!-1}{(1+r!)(1+(1+r)!)}\right]\\ \\ &=\sum_{r=1}^{2014}\left[r!\left( \dfrac{(r+1)}{1+(r+1)!}-\dfrac{1}{1+r!}\right)\right]\\ \\ &=\sum_{r=1}^{2014}\left[ \dfrac{(r+1)!}{1+(r+1)!}-\dfrac{r!}{1+r!}\right] \end{aligned}

Now, let f ( n ) = n ! 1 + n ! f(n)=\dfrac{n!}{1+n!}

So, S = r = 1 2014 [ f ( r + 1 ) f ( r ) ] = f ( 2 ) f ( 1 ) + f ( 3 ) f ( 2 ) + + f ( 2015 ) f ( 2014 ) = f ( 2015 ) f ( 1 ) = 2015 ! 1 + 2015 ! 1 ! 1 + 1 ! = 2015 ! 1 + 2015 ! 1 2 \begin{aligned} S&=\sum_{r=1}^{2014} \left[f(r+1)-f(r)\right]\\ \\ &=f(2)-f(1)+f(3)-f(2)+ \cdots +f(2015)-f(2014)\\ \\ &=f(2015)-f(1)\\ \\ &=\dfrac{2015!}{1+2015!}-\dfrac{1!}{1+1!}\\ \\ &= \boxed{\dfrac{2015!}{1+2015!}-\dfrac{1}{2}} \end{aligned}

Hence, A + B 2 C = 2015 + 1 2 2 = 504 \dfrac{A+B}{2C}=\dfrac{2015+1}{2\cdot 2}=\boxed{504}

r . r ! ( 1 + r ! ) ( 1 + ( r + 1 ) ! \frac{r.r!}{(1 + r!)(1+ (r +1)!}

( ( r + 1 ) 1 ) . r ! ( 1 + r ! ) ( 1 + ( r + 1 ) ! \frac{((r+1) - 1 ).r!}{(1 + r!)(1+ (r +1)!}

( r + 1 ) ! r ! ( 1 + r ! ) ( 1 + ( r + 1 ) ! \frac{(r + 1)! - r!}{(1 + r!)(1+ (r +1)!}

( r + 1 ) ! + 1 ( r ! + 1 ) ( 1 + r ! ) ( 1 + ( r + 1 ) ! \frac{ (r + 1)! + 1 - ( r! + 1)}{(1 + r!)(1+ (r +1)!}

1 1 + r ! 1 1 + ( r + 1 ) ! \frac{1}{1 + r!} - \frac{1}{1 + (r + 1)!}

now adding we get

1 2 1 1 + 2015 ! \frac{1}{2} - \frac{1}{1 + 2015!}

2015 ! 2. ( 1 + 2015 ! ) \frac{2015!}{2.(1 + 2015!)}

where i went wrong?

sandeep Rathod - 6 years, 7 months ago

Log in to reply

Nowhere. Subtract your result from my result to obtain 0 .

Pratik Shastri - 6 years, 7 months ago

Log in to reply

yes that's true but we had to compare . i lost my points though my solution was right!

sandeep Rathod - 6 years, 7 months ago

Log in to reply

@Sandeep Rathod You could have tried to get it into the form mentioned in the question, that's not tough. 1 2 1 1 + 2015 ! = 1 2 1 + 2015 ! 2015 ! 1 + 2015 ! = 1 2 1 + 2015 ! 1 + 2015 ! = 2015 ! 1 + 2015 ! 1 2 \begin{aligned} \dfrac{1}{2}-\dfrac{1}{1+2015!} &= \dfrac{1}{2}-\dfrac{1+2015!-2015!}{1+2015!}\\ &=\dfrac{1}{2}-1+\dfrac{2015!}{1+2015!}\\ &=\dfrac{2015!}{1+2015!}-\dfrac{1}{2} \end{aligned}

Pratik Shastri - 6 years, 7 months ago

Log in to reply

@Pratik Shastri Thank you a new thing learned question was really nice

sandeep Rathod - 6 years, 7 months ago

Log in to reply

@Sandeep Rathod @sandeep Rathod Cheers :)

Pratik Shastri - 6 years, 7 months ago

I did like Sandeep Sir. It took me more time to manipulate the result than to get it.

Abhishek Sharma - 6 years, 2 months ago

Where is Calculus used in the solution?

Star Light - 6 years, 5 months ago

Log in to reply

Sequences and series comes under calculus but in India is studied under algebra

U Z - 6 years, 4 months ago
William Chau
Dec 30, 2014

Note that k * k!/[(1+k!)(1+(k+1)!] = 1/(1+k!) - 1/[1+(k+1)!]. So

S

= 1/(1+1!)-1/(1+2!)+1/(1+2!)-1/(1+3!)+...+1/(1+2014!)-1/(1+2015!)

= 1/2-1/(1+2015!)

= (2015!-1)/[2(1+2015!)]

= 2015!/(1+2015!)-1/2.

Therefore A = 2015, B = 1, C = 2, and (A+B)/(2C) = 504.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...